Análisis de la herramienta de propaganda negra en Facebook: caso Falquez Aguilar 2019. - Chiriboga Cabrera, Jenniffer Thalia; Tinoco Astudillo, Diana Carolina (My University, 2020)
Since the beginning of a electoral contest, the people are exposed to countless messages from the electoral candidates. It’s in this momento where the social networks turn the black advertising into a powerful manipulation tool of information between the candidates, looking for some or another way demoralize and discredit the image of the opponent by misrepresenting information unknown to voters. This article has as purpose analyse the black advertising tool in Facebook, case Falquez Aguilar 2019 during election campaigns (February 5 - March 20), developing a mixed approach methodology with two investigative techniques: Content analysis, used for the analysis of the communicative message of the most relevant publications (by percentages of likes, comments and reactions); and Digital Ethnography, used to study user comments on selected posts; obtaining a total sample of 60 comments for the study. As a result, publications express attacks on the candidate's honor or dignity, mismanagement and corruption; As for comments, it denotes a critical attitude emphasizing distrust to the traditional political actors and political movements and parties; as well as, it also reflects a positive political attitude to Falquez Aguilar.
Desde el inicio de una contienda electoral, las personas están expuestas a un sinnúmero de mensajes por parte de los candidatos electorales. Es en este momento donde las redes sociales convierten a la propaganda negra en una poderosa herramienta de manipulación de información entre los candidatos, buscando de alguna u otra forma desmoralizar y desprestigiar la imagen del opositor al tergiversar información desconocida para los electores. Este artículo tiene como propósito analizar la herramienta de propaganda negra en Facebook, caso Falquez Aguilar 2019 durante las campañas electorales (05 de febrero – 20 de marzo), desarrollando una metodología de enfoque mixto con dos técnicas investigativas: Análisis de contenido, utilizada para el análisis del mensaje comunicativo de las publicaciones más relevantes (por porcentajes de likes, comentarios y reacciones); y Etnografía Digital, empleada para el estudio de los comentarios de usuarios en los posts seleccionados; obteniendo una muestra total de 60 comentarios para el estudio. Como resultado, las publicaciones expresan ataques al honor o dignidad del candidato, la mala administración y corrupción; en cuanto a comentarios, denota una actitud crítica enfatizando la desconfianza hacia actores políticos tradicionales y, movimientos y partidos políticos; así como, también refleja una actitud política positiva hacia Falquez Aguilar.
Keywords: MARKETING POLÍTICO; PROPAGANDA NEGRA; FACEBOOK